P0864PHYSICIAN ATTITUDES TOWARDS DIAGNOSING ANAEMIA, TREATMENT INITIATION AND THE CURRENT UNMET NEED IN THE MANAGEMENT AND TREATMENT OF ANAEMIA: INTERIM RESULTS FROM A CROSS-SECTIONAL REAL-WORLD SURVEY IN GERMANY, ITALY AND THE UK. (6th June 2020) - Kabra, Madhusudan; Hammond, Tim; Fleetwood, Allison; Harrison, Lewis; Moon, Rebecca; Jackson, James
Abstract: Background and Aims: Anaemia, a complication of chronic kidney disease (CKD), is commonly defined as serum haemoglobin (Hb) levels of <12 g/dL in women and <13 g/dL in men. Its prevalence and severity increase with the decline in renal function and it is often associated with a decreased quality of life (QoL), and an increase in number of hospitalisations and comorbidities. Traditionally, primary care physicians (PCPs) have less involvement managing patients with CKD anaemia and nephrologists have a greater role in treatment decisions. We describe current physician perception towards the diagnosis and treatment of anaemia and the current unmet need in anaemia management, in a real-world setting. Method: Preliminary data were drawn from the Adelphi CKD Disease Specific Programme TM, a point-in-time study conducted between November 2019 and January 2020 with nephrologists and PCPs from Germany, Italy and the United Kingdom. Physicians completed a detailed online survey providing information on their demographics, opinions on the diagnosis and treatment of anaemia, and the current unmet needs they believe exist in the management and treatment of anaemia. Results are based on interim data and analysed descriptively. Results: A total of 144 physicians (n=94 nephrologists; n=50 PCPs) were included in the analysis. Among those who responded, the majority used Hb levels to diagnose anaemia in CKD patients. Over two thirds of physicians mentioned using ferritin to diagnose anaemia and over half reported using transferrin saturation (TSAT) levels. Reported use of ferritin and TSAT testing was lower among PCPs. Three quarters of nephrologists and PCPs (76% of each respectively) reported Hb levels to be the most important factor that triggers initiation of anaemia treatment in CKD patients, followed by fatigue/weakness (53% of both nephrologists and PCPs) and overall health/QoL (29% nephrologists; 18% PCPs). Ferritin levels (24% of each respectively); TSAT levels (23% nephrologists; 24% PCPs) and shortness of breath (22% nephrologists; 24% PCPs) were also among the most important factors. The top three unmet needs in the management and treatment of CKD anaemia, as reported by nephrologists were: treatment for refractory/resistant patients (34%), lower cost of therapy (34%) and need for more oral treatments (33%). PCPs' top three unmet needs were reported as: treatment for refractory/resistant patients (42%), fewer side effects (42%) and need for more oral treatments (34%). Differences observed between nephrologists and PCPs related to a need for alternative treatments (19% nephrologists; 26% PCPs), access to ESA treatment (17% nephrologists; 30% PCPs) and treatments with lower risk of CV events (26% nephrologists; 12% PCPs). Conclusion: This data reinforced that Hb levels, ahead of ferritin and TSAT levels have an important role in the diagnosis and initial prescription of therapy for anaemia in CKD patients. It also highlighted an unmet need for treatment of refractory/resistant patients and the desire among both nephrologists and PCPs for safer and affordable novel treatments for anaemia patients.